The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1149/2.0071605jss
|View full text |Cite
|
Sign up to set email alerts
|

Red Shift of CT-Band in Cubic Y2O3:Eu3+upon Increasing the Eu3+Concentration

Abstract: In this article we describe the redshift of the charge transfer band of nanosized cubic (Y 1−x Eu x ) 2 O 3 upon increasing the Eu 3+ concentration. This redshift amounts to 0.43 eV (25 nm) in going from 0.1 Mol % Eu 3+ to 100 Mol % (which is pure Eu 2 O 3 ). The charge transfer band consists of two broad sub-bands; both shift almost parallel with the Eu 3+ concentration and are related to the two symmetry sites for the cation, C 2 and C 3i , in the bixbyite-type lattice. The area ratio of the bands is 3:1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Due to fundamental and technological importance, the charge-transfer (CT) phenomenon has been a key area of research. For technologically important rare-earth ions like Eu 3+ , which inherently have poor excitation efficiency, charge transfer plays a central role in governing their luminescent properties . CTB is useful for sensitization of Eu 3+ luminescence, because it can act as an antenna to absorb incoming light and then transfer excitation energy to the Eu 3+ ion, in a way similar to sensitization by organic chromophores. Common Eu 3+ phosphors have broad CTB of O 2– → Eu 3+ originating due to transfers of an electron from a neighboring oxygen 2p orbital to an empty 4f orbital of Eu 3+ ion. ,, Previously, many attempts have been made to find factors influencing CT energy (i.e., the position of CTB in the excitation spectra) both qualitatively and quantitatively. , In these investigations, CTB has been found to be dependent on host structure, sites occupied by Eu 3+ ion in the host matrix, ionicity/covalency of Eu–O bond, position of the valence band/electronic structure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Due to fundamental and technological importance, the charge-transfer (CT) phenomenon has been a key area of research. For technologically important rare-earth ions like Eu 3+ , which inherently have poor excitation efficiency, charge transfer plays a central role in governing their luminescent properties . CTB is useful for sensitization of Eu 3+ luminescence, because it can act as an antenna to absorb incoming light and then transfer excitation energy to the Eu 3+ ion, in a way similar to sensitization by organic chromophores. Common Eu 3+ phosphors have broad CTB of O 2– → Eu 3+ originating due to transfers of an electron from a neighboring oxygen 2p orbital to an empty 4f orbital of Eu 3+ ion. ,, Previously, many attempts have been made to find factors influencing CT energy (i.e., the position of CTB in the excitation spectra) both qualitatively and quantitatively. , In these investigations, CTB has been found to be dependent on host structure, sites occupied by Eu 3+ ion in the host matrix, ionicity/covalency of Eu–O bond, position of the valence band/electronic structure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, amorphous local structures around Eu 3+ provide lower excitation energy in CTB around 250 nm due to longer EuO bonding length. 20)…”
Section: Resultsmentioning
confidence: 99%
“…In ref. 24 we have suggested that this could be caused by a difference in compressibility between the Y 2 O 2 S:Tb 3+ and the Gd 2 O 2 S:Tb 3+ lattices. In this reference we have already mentioned that the proposed electrostatic model in terms of the Madelung energy leads to a similar result as the chemical shi model proposed by Dorenbos.…”
Section: Redshi Of Ct-bandmentioning
confidence: 88%
“…Recently we have introduced an electrostatic model in terms of the Madelung energy of the transferred charge that could quantitatively describe the red shi of the CT-band in Y 2 O 3 :Eu 3+ . 24 This model will now be applied to the data presented in Fig. 6a 25 The charge transfer during excitation of a photon can be represented by the following reaction:…”
Section: Redshi Of Ct-bandmentioning
confidence: 99%
See 1 more Smart Citation